2012
DOI: 10.1111/j.1742-7843.2012.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carvedilol and Nebivolol on Oxidative Stress‐related Parameters and Endothelial Function in Patients with Essential Hypertension

Abstract: Oxidative stress and endothelial dysfunction have been associated with essential hypertension (EH) mechanisms. The purpose of this study was to evaluate the effect of carvedilol and nebivolol on the oxidative stress-related parameters and endothelial function in patients with EH. The studied population included 57 patients, either sex, between 30 and 75 years of age, with mild-to-moderate EH complications. Participants were randomized to receive either carvedilol (12.5 mg) (n = 23) or nebivolol (5 mg) (n = 21)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 49 publications
2
48
1
1
Order By: Relevance
“…In hypertensive patients, treatment with Nebivolol for 12 weeks did not improve the total antioxidant status as compared to carvedilol. 11 Although the patients in our group had coronary artery disease and hypertension, these findings are in support of our data. On contrary, Nebivolol given for eight months in patients with heart failure and diabetes, showed a significant improvement in antioxidant protection as assessed by increase in SH group level.…”
Section: Discussionsupporting
confidence: 82%
“…In hypertensive patients, treatment with Nebivolol for 12 weeks did not improve the total antioxidant status as compared to carvedilol. 11 Although the patients in our group had coronary artery disease and hypertension, these findings are in support of our data. On contrary, Nebivolol given for eight months in patients with heart failure and diabetes, showed a significant improvement in antioxidant protection as assessed by increase in SH group level.…”
Section: Discussionsupporting
confidence: 82%
“…Although the exact mechanism of carvedilol beneficial effects has not been fully understood, it seems that carvedilol exerts its effect through OS markers normalization (lipid peroxides, nitric oxide, and protein thiols) and lowers the release of inflammatory cytokines such as TNF-a, interleukin-6 (IL-6), and eicosanoids (Arab & El-Sawalhi, 2013), suggesting its beneficial effects in hyper-inflammation (Mizuochi et al, 2007) and reducing OS (Oettl et al, 2001;Ouyang et al, 2013;Zepeda et al, 2012). The hydroxylated compounds of SB 211475, BM 910228, and SB 209995 as carvedilol's main metabolites exert the greatest antioxidant activity, which may be responsible for carvedilol protective effect (Lysko et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A forest plot illustrating the comparison between 3 rd and 2 nd generation of beta-blockers is shown in Figure 2B. In addition to a 3 rd and 2 nd generation comparison, Zepeda et al [14] also compared with each other the effects of two 3 rd generation beta-blockers: carvedilol and nebivolol. The two agents gave a similar improvement of FMD, with a MD of: 3.75 ± 8.67 for carvedilol and 4.7 ± Figure 2.…”
Section: Third Vs Second Generation Of Beta-blockersmentioning
confidence: 99%
“…In 12 studies, the cuff was placed on the forearm and in 3 studies measurements was performed with cuff placed on the arm [10][11][12]. Six studies reported the number of observers who assessed FMD [9,10,[13][14][15][16]. In 5 of those studies, only 1 person was responsible for the FMD measurements.…”
Section: Fmd Measurementsmentioning
confidence: 99%